DYNAMIC INTERRELATION BETWEEN STOCK MARKET INDEX, EXCHANGE RATE, T-BILLS AND POLICY RATE: THE CASE OF EGYPT 2010-2020 - El Kahky, Yara (PEOPLE: International Journal of Social Sciences, 2024)
A robust securities market is the engine of a country's economy. Undoubtedly, the stability and strength of a country's financial intermediaries and secondary market systems determine its overall economic growth. Since 2009, when the secondary market and Egypt’s EGX 30 stock index were established, the Egyptian economy has been on a trajectory of growth. However, Egypt's economy has been facing various economic and financial challenges in recent years because of political instability and social unrest, starting with the 2011 political revolution and the global external shocks such as the Corona pandemic, which negatively impacted its foreign capital inflows from the hard currency. Which made it essential and critical to ask for financial assistance from international institutions and the global financial market to maintain the country's economic wellbeing. That was linked to economic structural reform-backed loan programs and agreements with the IMF and the World Bank. Since then, it is assumed that Egypt’s economy is moving towards more cointegration with the global economy, especially after the IMF-backed loan program and the economic reforms that took place since the end of 2016 with the currency flotation regime in November 2016. Since then, Egypt’s economic stance, stock market, and foreign exchange rate turned out to be more reflective and vulnerable to the external shocks that are taking place. And with the association of the IMF loan program, the financial capital market via foreign capital inflows in the foreign portfolio investments, has played a main role in influencing the currency performance through Egypt’s equity and debt markets, which are directly and indirectly influenced by Egypt’s Central Bank monetary policy decisions. This paper helps to understand the stock, foreign exchange markets in Egypt and the impact of the government’s monetary policy on the financial market. It aims at identifying the determinants of both markets, investigates the relationship between macroeconomic variables on Egypt’s EGX30 all-share stock index and Egypt’s FX rate. The macroeconomic interrelations are examined including Egypt’s lending interest rate and the 91-day Treasury bill (T-bill) rate. By applying the cointegration model and the VECM model to test the short-run and long-run relationships between the noted variables. The findings indicated a long-run relationship between Egypt's stock market index, lending rates, and T-bills over the period from 2010 until 2016, before the currency flotation regime.